Activation asymmetry of the lateral abdominal muscles in response to neurodevelopmental traction technique in children with pelvic asymmetry - Polaczek Agnieszka; Szlachta Grzegorz (Biomedical Human Kinetics, 2023)
Study aim: The aim of the study was to evaluate asymmetry of activation of lateral abdominal muscles (LAM) in response to neurodevelopmental traction technique in children with pelvic asymmetry.